Enhancing Vocational Students’ Socio-Emotional Adjustment through Artificial Intelligence Supported Learning - Sari Indrayani; Rita Nur Anjani (CV. FoundAE, 2026)
Artificial intelligence (AI) is increasingly embedded in school learning environments, yet evidence remains limited on its developmental value in vocational secondary education. This quasi-experimental study examined whether an eight-week AI-supported socio-emotional learning and AI literacy intervention was associated with improved socio-emotional adjustment, AI literacy, and perceived AI support among vocational students. A non-equivalent pretest-posttest control-group design was implemented with 168 Grade 10–11 students from four intact classes in two public vocational schools in Way Kanan, Indonesia. The AI-supported condition (n = 84) received activities integrating AI literacy, reflective prompting, feedback evaluation, peer dialogue, and teacher-mediated socio-emotional reflection, while the comparison condition (n = 84) received regular technology-enriched instruction. ANCOVA controlling for pretest scores showed higher adjusted posttest scores in the AI-supported condition for socio-emotional adjustment, F(1,165) = 18.72, p < .001, partial η² = .102; AI literacy, F(1,165) = 44.96, p < .001, partial η² = .214; and perceived AI support, F(1,165) = 16.84, p < .001, partial η² = .093. Findings suggest that structured, teacher-guided AI learning may support vocational students’ socio-emotional and AI-related development, although intact-class assignment and self-report outcomes require cautious interpretation.